Singapore : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes quality upgrading and low-wage competition for Singapore. The analysis concludes that quality upgrading is indeed taking place in some products where low-wage competitors are entering. More generally, Singapore's exports are of a higher quality than its regional competitors, and the quality gap has widened over time. This paper also assesses the factors behind the mixed results of Singapore banks' outward expansion by examining the region's industry structure and competitive conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet